Analysis of the Transmission Scheme of CR-CR Planetary Gear Mechanism based on Line Velocity Vector Method - Liu Chenfu; Zhang Yushu; Qin Yongjie (Jixie chuandong)
The rotation direction and speed of each element in the planetary gear mechanism can be directly shown by drawing the linear velocity vector diagram of the gear ring,planet carrier and sun wheel in the CR-CR planetary gear mechanism. The transmission ratio of typical transmission scheme is calculated by geometric method based on the obtained line speed vector diagram,which is exactly the same with the transmission ratio calculated by analytical method. The correctness and feasibility of analyzing the transmission scheme of CR-CR planetary gear mechanism by line velocity vector method is verified.